Geometric–Statistical Model for Middle-Ear Anatomy and Ventilation - Marian Rădulescu; Adela-Ioana Mocanu; Ionela Teodora Dascălu; Mihai-Adrian Schipor; Horia Mocanu (Applied Sciences, 2022)
The ventilation of the middle-ear (ME) is achieved by the mucosa covering the bony cavities of this segment, which we have previously defined as consisting of two distinct epithelial areas, each representing an independent organ with characteristic function: the D-Organ and the F-Organ. The D-Organ corresponds to the epithelium covering the Antrum walls (belonging to the central cavities of the middle-ear) and the walls of mastoid and petrous cavities (peripheral cavities of the ME); it ensures the D-Function, the biophysical process comparable to that of energy-consuming ionic membrane pumps, works against electrical trans-membrane gradients to transfer gas molecules against trans-membrane and trans-cellular pressure gradients. The F-Organ corresponds to the epithelium covering the Protympanum, Tympanic Cavity and Aditus ad Antrum (central cavities of ME). The F-Function is represented by the permeability of cell membranes for respiratory gases. This is a general function of all cells and the size of the cellular membrane surface (luminal and basal) and the height of the cell (distance between the two membranes) determines the diffusion flow for each molecular type of gas. The present work aims to give an original point of view on middle-ear geometry and precedence over ME mucosa affliction or structural-anatomic type of the mastoid (pneumatic, pneumato-diploic, diploic, sclerotic). This type of approach to the problem has never been attempted since the two organs have never been previously defined. We aim to establish a clear topographic structure for these two organs within the reference system represented by the anatomy of ME cavities and to establish the reasons why the mastoid and petrous cavitary system grow or stop growing at a certain point in the life of an individual.